Kecerdasan Spiritual dan Kebahagiaan Pada Narapidana Wanita - Condinata, Frida; Elvinawanty, Rianda; Marpaung, Winida (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2019)
Abstract Happy life is everyone's hope, but happiness is influenced by many factors. This study aims to determine the relationship between spiritual intelligence and happiness. The subjects of this study were female inmates at the Class IIA Medan Women's Penitentiary of 186 people. The research data was obtained using a scale of spiritual intelligence and happiness. The data analysis used is Product Moment correlation through SPSS 18 for Windows. The results of data analysis showed a correlation coefficient of 0.664 and a significance value of 0.000 (p <0.05). This shows there is a positive relationship between spiritual intelligence and happiness. The results of this study indicate that the contribution given by the variable spiritual intelligence to happiness is 44.1 percent, the rest 55.9 percent is influenced by other factors not examined. It can be concluded that spiritual intelligence has a big influence on the happiness of female prisoners.Keywords: Happiness, Spiritual Intelligence Abstrak Hidup bahagia adalah harapan semua orang, namun demikian kebahagiaan dipengaruhi oleh banyak faktor. Penelitian ini bertujuan untuk mengetahui hubungan antara kecerdasan spiritual dengan kebahagiaan. Subjek penelitian ini adalah narapidana wanita di Lembaga Pemasyarakatan Perempuan Kelas IIA Medan sebanyak 186 orang. Data penelitian diperoleh menggunakan skala kecerdasan spiritual dan kebahagiaan. Analisis data yang digunakan adalah korelasi Product Moment melalui bantuan SPSS 18 for Windows. Hasil analisis data menunjukkan koefisien korelasi sebesar 0,664 dan nilai signifikansi sebesar 0,000 (p<0,05). Ini menunjukkan ada hubungan positif antara kecerdasan spiritual dengan kebahagiaan. Hasil penelitian ini menunjukkan bahwa sumbangan yang diberikan variabel kecerdasan spiritual terhadap kebahagiaan sebesar 44,1 persen, selebihnya 55,9 persen dipengaruhi oleh faktor lain yang tidak diteliti. Dapat disimpulkan kecerdasan spiritual memiliki pengaruh yang besar terhadap kebahagiaan narapidana wanita.Kata kunci: Kebahagiaan, Kecerdasan Spiritual